THE INFLUENCE OF ORGANIZATIONAL FACTORS AND INDIVIDUAL FACTORS ON WORK STRESS IN EMPLOYEES OF PT. LION MENTARI PADANG - Susanti, Febsri; Junita, Rani (LPPM Universitas Bina Bangsa, 2022)
This study aimed to determine and analyze the effect of organizational factors and individual factors on work stress on employessof PT. Lion Mentari Padang. The population in this study were all employees of PT. Lion Mentari Padang, totaling 80 people. The sampling technique used is saturated sample. Because the population in this study was relatively small, and less than a hundred people, the entire population could be sampled. The data analysis technique used to test the hypothesis is the statistical t test. The results showed that organizational factors affects work stress of employees of PT. Lion Mentari Padang. This is because organizational factors has a significant value of 0.005, this significant value is smaller than alpha 0.05. This means that organizational factors has a significant effect on work stress. Individual factors affect on work stress of employees of PT. Lion Mentari Padang. This is because individual factors have a significant value of 0.000, this significant value is smaller than alpha 0.05. This means that individual factors have a significant effect on work stress